Persepsi Wisatawan Lokal pada Interior Onshore Floating Resort - Nastiti, Ratna Andriani; Ayuswantana, Alfian Candra; Tanadda, Onna Anieko; Fata, Ibrahim; Herwina, Nevlin Cresentia; Dini, Mazaya Islami (Waca Cipta Ruang, 2024)
The concept of healing has gained significant popularity in Indonesia, particularly in light of the recent surge in Covid-19 cases. The term "healing" has gained popularity in Google searches as a replacement for the term "traveling". An intriguing therapeutic retreat is the Bee Jay Bakau Resort, located in Probolinggo. One notable coastal destination with promising potential is the floating resort. In general, floating resorts offer distinctive accommodations that provide a unique experience of being on the sea. Tourists can immerse themselves in the oceanic lifestyle, enjoying panoramic views and the company of marine fauna. The aforementioned experience can be imparted to tourists through the aid of a captivating and unforgettable floating interior design. The objective of the research is to identify visual elements that can impact tourists' perception while inside the floating resort. The study will utilize a qualitative descriptive method, employing the snowball sampling approach to recruit participants. Data acquisition is accomplished through the utilization of the semi-structured interview technique to get information from respondents. The study findings revealed variations in the perspective of individual tourists, with a predominant emphasis on the visual elements of the interior. Moreover, the outcomes of this study are anticipated to serve as a standard for developing interior designs for floating resorts, particularly in the context of a post-pandemic environment.